The Effect of Green Accounting Implementation on Profitability in Companies Compass Index 100 - Budiono, Slamet; Dura, Justita (CV. Inara, 2021)
In the Kompas100 Index Company, there are several companies whose growth can have a positive or negative impact on the surrounding environment, so companies need to provide information related to green accounting. This study was conducted to determine the application of green accounting and its impact on company profitability. In this study, the application of green accounting as measured by the Company Performance Rating Program in Environmental Management (PROPER) on the level of profitability with the ROA (Return on Assets) indicator. The research method used is quantitative research methods. The population selected in the study of 100 Kompas Index companies for 2 years in 2018-2019 using the purposive sampling method, to obtain a sample of 24 companies that meet the criteria. Data were analyzed using simple regression. The results of this study indicate that the application of green accounting has a significant effect on the profitability of the Kompas100 Index company